Variation in body size of terrestrial isopods (Crustacea: Oniscidea) and application of ecogeographical rules - Καραγκούνη, Μαρία (2010)
Body size is the most important feature of all organisms and in this study is represented by the variables “body length” and “body width”. Bergmann’s Rule is a hypothesis concerning body size increase with latitude for homeotherms, whereas geographic version of Rensch’s Rule predicts greater body size variation with latitude for males. The trend predicted by the first rule is confirmed here for a group of ectotherms, terrestrial isopods, while that predicted by the second was not found to apply in these organisms. Several hypotheses have been proposed to explain body size variation in terms of environmental factors and interspecific interactions underlying latitudinal gradients. Thus, we used our results to test certain hypotheses proposed to account for Bergmann’s Rule. The Island Rule examines body size as it is affected by spatial parameters and reflects a complex pattern from gigantism in taxa with small sized mainland relatives, to dwarfism in taxa with large mainland relatives. Our results are not conclusive regarding this rule, but are indicative of trends that need to be examined in the future.